„U nas adin prokuror czestnyj czeławiek, a i on — prawdu skazat’ — swinia” — „rossica” w felietonistyce Stanisława Michalkiewicza - Dzienisiewicz, Daniel (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article aims at presenting and analyzing rossica (linguistic and culturalborrowings from Russian) retrieved from the texts written by Stanisław Michalkiewicz. Stanisław Michalkiewicz is a conservative-liberal author and a former politician. Along with borrowings from Latin and French, Michalkiewicz, known for his command of Russian, incorporates various Russian and Soviet linguistic and cultural elements in his writings. Rossica come in the form of lexical and textual borrowings, e.g. quotations from politicians, literary works, popular songs and jokes. One can also distinguish indirect sources of rossica, such as quotations from Polish literary works referring to Russian reality. Moreover, Michalkiewicz creates original derivates of Russian borrowings and modifies the forms of dative case of Polish personal names according to the Russian masculine noun declension paradigm.